Formation Of nurses at Universidad de Antioquia : A reality embodied in its study plans (2020)
ABSTRACT: The article presents the trajectory of the study plans that have guided the formation of nursing professionals at Universidad de Antioquia in Medellín (Colombia). It presents the principal milestones or events that at a given moment determined significant ruptures in the formation processes and which show how this Faculty of Nursing, in its 70 years of existence, has always articulated the health needs of the context with the formulation of its study plans, with the sole purpose of forming critical and innovative nursing professionals capable of responding assertively to care needs, according with the principal challenges or trends that condition the health environment.